2015
DOI: 10.1016/j.tvjl.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of altered distances between obstacles on the jump kinematics and apparent joint angulations of large agility dogs

Abstract: Highlights 17 In contrast to equines, canine sport science has been poorly studied. 18 As the distance between consecutive upright hurdles increases, so do the take-off and 19 landing distances. 20 Take-off and landing distances further alter with the dog's skill level. 21 There are greater differences in jump kinematics when the distances between 22 consecutive hurdles are shorter. speeds differed for hurdle distances (P < 0.001) and level of skill (P < 0.001). There were 40 significant differences in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 15 publications
3
32
2
Order By: Relevance
“…Whilst ID movement is very similar to EDs, the exaggerated flexion recorded in atlas (C1) and L3 during kinematic evaluation corresponds to IDs moving their head more and looking over the apex before completing it, which could be a manifestation of their unrefined technique, a lack of refined motor skills, apprehension, excitement or distraction (seeking handler) due to their inexperience. Birch et al (2015) also found IDs exhibited different kinematic profiles compared to EDs when jumping a hurdle. The impact of training on kinematic parameters has been explored in showjumping horses.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Whilst ID movement is very similar to EDs, the exaggerated flexion recorded in atlas (C1) and L3 during kinematic evaluation corresponds to IDs moving their head more and looking over the apex before completing it, which could be a manifestation of their unrefined technique, a lack of refined motor skills, apprehension, excitement or distraction (seeking handler) due to their inexperience. Birch et al (2015) also found IDs exhibited different kinematic profiles compared to EDs when jumping a hurdle. The impact of training on kinematic parameters has been explored in showjumping horses.…”
Section: Discussionmentioning
confidence: 87%
“…The variation observed in the forelimb joint angles recorded, mirrors the role of the forelimb during the five phases of the A-Frame. Individual differences occur between dogs and are attributed to different methods of approach including speed, different take off locations and the length of time the dog spends in suspension over the apex (Birch et al, 2015;Pfau et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The study was undertaken in accordance with Birch et al, (2015), analysing data collected at assessed inter-observer reliability and one way analysis of variance (ANOVA) was used to 102 assess for any differences. Tukey's post hoc tests determined where the differences lay with 103 means (± standard error) used to report these differences.…”
mentioning
confidence: 99%
“…Hurdle height has been shown to affect vertical peak force and landing angle (Pfau et al, 2011) and joint angles of the forelimb and hindlimb at take-off (Birch and Le sniak, 2013). The type of obstacle and the distance between them influences the peak vertical force, the vertical momentum, the accelerating horizontal momentum during landing (Pfau et al, 2011), the speed and the jumping distance (Birch et al, 2015). Furthermore, the peak vertical force depends on the breed of dog (Yanoff et al, 1992).…”
Section: Introductionmentioning
confidence: 99%